Effect of Adapted Ergometer Setup and Rowing Speed on Lower Extremity Loading in People with and Without Spinal Cord Injury - Ying Fang; Karen L. Troy (Bioengineering)
Background: Functional electrical stimulation-assisted rowing (FES rowing) is a rehabilitation exercise used to prevent disuse osteoporosis, which is common in people with spinal cord injury (SCI). However, its effect on bone loss prevention varied in SCI patients, potentially due to inconsistent loading. This study investigates the effect of ergometer setup and rowing speed on lower extremity loading during rowing. Methods: Twenty able-bodied participants and one participant with SCI rowed on an adapted ergometer with different speeds and setups. We calculated foot reaction force and knee moment for all participants, and tibiofemoral force for the rower with SCI. Results: Able-bodied rowers generated 0.22–0.45 body weight (BW) foot reaction forces, and a higher force was associated with a fast speed, forward seat position, and large knee range of motion (RoM). The rower with SCI had the greatest foot reaction force (0.39 BW) when rowing with a small knee RoM at a rear seat position, and the highest tibiofemoral force (2.23 BW) with a large knee RoM or at a rear seat position. Conclusions: Ergometer setup and speed both affect lower limb loading and should be further studied in more rowers with SCI. This can inform rehabilitation protocols to standardize ergometer configuration to improve bone health.